Consequences of Stabilizing the Natively Disordered F helix for the Folding Pathway of Apomyoglobin - Nishimura, Chiaki (2011)
The F helix region of sperm whale apomyoglobin (apoMb) is disordered, undergoing conformational fluctuations between a folded helical conformation and one or more locally unfolded states. In order to examine the effects of F helix stabilization on the folding pathway of apoMb, we have introduced mutations to augment intrinsic helical structure in the F helix of the kinetic folding intermediate and to increase its propensity to fold early in the pathway, using predictions based on plots of the average area buried upon folding (AABUF) derived from the primary sequence. Two mutant proteins were prepared, a double mutant P88K/S92K (F2) and a quadruple mutant, P88K/A90L/S92K/A94L (F4). Whereas the AABUF for F2 predicts that the F helix will not fold early in the pathway, the F helix in F4 shows a significantly increased AABUF and is therefore predicted to fold early. Protection of amide protons by formation of hydrogen-bonded helical structure during the early folding events has been analyzed by pH-pulse labeling. Consistent with the AABUF prediction, many of the F helix residues for F4 are significantly protected in the kinetic intermediate but are not protected in the F2 mutant. F4 folds via a kinetically trapped burst phase intermediate that contains stabilized secondary structure in the A, B, F, G, and H helix regions. Rapid folding of the F helix stabilizes the central core of the misfolded intermediate and inhibits translocation of the H helix back to its native position, thereby decreasing the overall folding rate.